1999
DOI: 10.1074/jbc.274.43.30864
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Signaling Properties of the Cytoplasmic Domains of the Insulin Receptor and Insulin-like Growth Factor Receptor in 3T3-L1 Adipocytes

Abstract: Insulin and insulin-like growth factors (IGFs) elicit distinct but overlapping biological effects in vivo. To investigate whether differences in intrinsic signaling capacity of receptors contribute to biological specificity, we constructed chimeric receptors containing the extracellular portion of the neurotrophin receptor TrkC fused to the intracellular portion of the insulin or IGF-I receptors. Chimeras were stably expressed in 3T3-L1 adipocytes at levels comparable to endogenous insulin receptors and were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 66 publications
(74 reference statements)
7
34
1
Order By: Relevance
“…To examine whether AA might have an effect on levels of GLUT1 or GLUT4 at the plasma membrane the plasma membrane lawn assay was used. Insulin treatment of 3T3-L1 cells produced an ϳ2-fold increase in GLUT1 and a 5-fold increase in GLUT4 plasma membrane expression, results which are consistent with previous published studies (33). AA increased levels of GLUT1 at the plasma membrane in the absence and presence of insulin by 2-(p Ͻ 0.05) and 1.3-fold (p Ͻ 0.001), respectively, and increased levels of GLUT4 at the plasma membrane in the absence and presence of insulin by 1.5-fold (p Ͻ 0.01) and 1.4-fold (p Ͻ 0.05), respectively (Fig.…”
Section: Effect Of Arachidonic Acid On the Expression And Cellular Losupporting
confidence: 81%
See 1 more Smart Citation
“…To examine whether AA might have an effect on levels of GLUT1 or GLUT4 at the plasma membrane the plasma membrane lawn assay was used. Insulin treatment of 3T3-L1 cells produced an ϳ2-fold increase in GLUT1 and a 5-fold increase in GLUT4 plasma membrane expression, results which are consistent with previous published studies (33). AA increased levels of GLUT1 at the plasma membrane in the absence and presence of insulin by 2-(p Ͻ 0.05) and 1.3-fold (p Ͻ 0.001), respectively, and increased levels of GLUT4 at the plasma membrane in the absence and presence of insulin by 1.5-fold (p Ͻ 0.01) and 1.4-fold (p Ͻ 0.05), respectively (Fig.…”
Section: Effect Of Arachidonic Acid On the Expression And Cellular Losupporting
confidence: 81%
“…For the 1-h time point, cells were starved for 1 h prior to incubation in the AA medium. Glucose uptake assays were performed as described previously (33).…”
Section: Materials-2-deoxy-d-mentioning
confidence: 99%
“…Fewer mRNAs (11) were differentially regulated compared with those similarly regulated between the two cell lines, consistent with the broadly overlapping effects of insulin and IGF-1 (Table II). Of the 11 differentially regulated transcripts, 1 was an EST that was suppressed to a greater extent by the TIR.…”
Section: Tigr Chimera Signaling Stimulates Transcription To Asupporting
confidence: 52%
“…We further demonstrated that MAPK is needed for TIGR signaling to HB-EGF, a requirement also observed in the IGF-1R-selective stimulation of Twist and VEGF transcription (28,29). In our study, MAPK was capable of being activated by both chimeric receptors, whereas other studies (11) 2 showed greater phosphorylation of MAPK in response to TIGR signaling. However, the relative differences in MAPK phosphorylation seen in those studies are unlikely to be sufficient to account for the all-or-nothing response we have 2 A. Parmar and K. Siddle, unpublished data.…”
Section: Fig 4 Signaling Pathways To Hb-egf Gene Expression In 3t3-contrasting
confidence: 47%
See 1 more Smart Citation